European practice of state officials actions: evolution of approaches - Havrylyuk, Ruslana (Polish academy of sciences institute of geography and spatial organization, 2004)
Under the influence of transformations in post-socialist republics since the start of democratic evolutionary processes, it would be useful to substantiate the legitimacy of the conceal coming back from XIX c. that state accountability for its officials’ activities is based on public fundamentals and formed on the principle of protection of not only individual interests but public also. Complexity of the problem of state accountability is brought about by other numerous problems of a more common legal character requiring prior solution. Some of the issues concern civil law, for example: 1. What is indemnification? 2. What are the conditions of possible accountability for actions of others? 3. Whether and when is accountability possible in the absence of guilt?
Keywords: obligation; theory of extra-contract; theory of professional risk; theory of state law; public law; classification of theories